Cost Optimization of a M/M/1/Wv&Mav Queueing System Using Newton-Raphson and Particle Swarm Optimization Techniques - Ramachandran Remya; Amina Angelika Bouchentouf; Kaliappan Kalidass (Operations Research and Decisions)
This paper is concerned with the optimal control of a Markovian queueing system subjected to multiple adaptive vacation and working vacation policies. This system is applicable in diverse modern technologies, in particular in call centers. We establish the steady-state solution as well as important system characteristics by means of probability generating functions technique. We also construct the expected total cost for this model and develop a procedure to determine the optimal service rate that yields the minimum cost. Further, we carried out a comparative analysis to obtain the minimum cost using the Newton-Raphson method and particle swarm optimization (PSO) algorithm. (original abstract)